Heritable capture of heterochromatin dynamics in Saccharomyces cerevisiae - Dodson, Anne E; Rine, Jasper (eLife, 2015)
Heterochromatin exerts a heritable form of eukaryotic gene repression and contributes to chromosome segregation fidelity and genome stability. However, to date there has been no quantitative evaluation of the stability of heterochromatic gene repression. We designed a genetic strategy to capture transient losses of gene silencing in Saccharomyces as permanent, heritable changes in genotype and phenotype. This approach revealed rare transcription within heterochromatin that occurred in approximately 1/1000 cell divisions. In concordance with multiple lines of evidence suggesting these events were rare and transient, single-molecule RNA FISH showed that transcription was limited. The ability to monitor fluctuations in heterochromatic repression uncovered previously unappreciated roles for Sir1, a silencing establishment factor, in the maintenance and/or inheritance of silencing. In addition, we identified the sirtuin Hst3 and its histone target as contributors to the stability of the silenced state. These approaches revealed dynamics of a heterochromatin function that have been heretofore inaccessible. A single cell from a plant, an animal or another eukaryote can contain several meters of DNA. In order to fit this length inside the nucleus of the cell, the DNA is wrapped around proteins called histones to form a compact structure known as chromatin. Chromatin exists in two forms: loosely packed chromatin tends to contain the genes that are expressed in cells, whereas highly compacted chromatin (also called heterochromatin) silences the expression of most nearby genes. Adding small chemical markings to histone proteins can alter how much the chromatin is compacted, and newly formed cells can inherit these markings whenever a cell divides. This enables the new cell to essentially ‘remember’ which genes were active and which were repressed in the original cell. However, no one has measured how stable heterochromatin is over multiple cell divisions; as such it is unclear if genes that should remain silent are occasionally expressed after a cell has divided a number of times. Budding yeast is a well-established model for studying heterochromatin. The genome of this single-celled organism has distinct regions of highly compacted chromatin, which are established and maintained by a number of different proteins. Dodson and Rine have developed a new technique to detect when gene silencing is lost in individual yeast cells, even if the loss of silencing only occurs for a brief period. This approach revealed that genes in supposedly ‘silent’ heterochromatin were still expressed but only very rarely—in about 1 in every 1000 cell divisions. Dodson and Rine's findings suggest that when silencing is lost, it is promptly re-established with the aid of a protein called Sir1. In addition, the new technique revealed that Sir1 helps to prevent losses of silencing in the first place. As such, the Sir1 protein appears to have previously unappreciated roles in the maintenance and the inheritance of heterochromatin in dividing yeast cells. Dodson and Rine also discovered that a protein called Hst3—which acts to remove chemical markings from histone proteins—also helps stabilize the silenced state. With this technique in hand, it is now possible to test any molecule, environment, or cellular process for its potential effect on the stability of gene silencing.